2010
DOI: 10.1007/s00467-010-1554-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-streptococcal acute glomerulonephritis in children: clinical features and pathogenesis

Abstract: Post-streptococcal acute glomerulonephritis (PSAGN) is one of the most important and intriguing conditions in the discipline of pediatric nephrology. Although the eventual outcome is excellent in most cases, PSAGN remains an important cause of acute renal failure and hospitalization for children in both developed and underdeveloped areas. The purpose of this review is to describe both the typical and less common clinical features of PSAGN, to outline the changes in the epidemiology of PSAGN over the past 50 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0
57

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(195 citation statements)
references
References 157 publications
(166 reference statements)
3
122
0
57
Order By: Relevance
“…22 The long-term implications of APSGN are less clear with studies reporting mixed outcomes. 23 Although many studies have reported favorable outcomes, some are less reassuring, especially in the Indigenous Australian population. A recent study has found significantly higher rates of albuminuria in Indigenous Australians with previous APSGN compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…22 The long-term implications of APSGN are less clear with studies reporting mixed outcomes. 23 Although many studies have reported favorable outcomes, some are less reassuring, especially in the Indigenous Australian population. A recent study has found significantly higher rates of albuminuria in Indigenous Australians with previous APSGN compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Postinfectious GN is a form of GN that develops after an infection; it is especially common in children and in the elderly (1)(2)(3)(4). Often the infection is minor (e.g., pharyngitis) and has usually resolved by the time clinical evidence of an ongoing GN is manifested.…”
Section: Discussion Of Questionmentioning
confidence: 99%
“…Nevertheless, it has been proposed that the initial phase of the process is characterized by deposition of bacterial antigens (e.g., streptococcal) in the glomeruli (planted). This phase is followed by production of antibodies that interact in situ with the planted antigens (2,9). Antigens that enter the circulation after the antibody response is fully underway form immune complexes in circulation.…”
Section: Discussion Of Questionmentioning
confidence: 99%
“…Anemia is common in APSGN and traditionally it has been attributed solely to volume overload (Eison et al, 2011). However, autoimmune hemolytic anemia (AIHA) has recently been reported in patients with APSGN.…”
Section: Autoimmune Hemolytic Anemiamentioning
confidence: 99%